1992
DOI: 10.1016/0925-9635(92)90109-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boron doping on the surface morphology and structural imperfections of diamond films

Abstract: This paper reports the surface morphology and structural imperfection of boron-doped diamond films prepared by microwave plasma enhanced chemical vapor deposition. It was found that boron dopants improved the structural quality of diamond films. The surface morphology consisted mainly of the { 111 } facets. A significant enhancement of nucleation density and consequent decrease of grain size was observed with the addition of diborane in the gas phase. Raman spectroscopy indicated that, with the introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…This is a source of contamination in the gas phase which leads to boron doping of the diamond films [9]. As shown by Wang et al [10], the addition of boron compounds in a microwaveplasma-assisted CVD system changes the surface morphology and the defect structure of the growing crystallites. Although during the present experiments no clear relation between surface structure and boron content was found, it cannot be excluded that the observed morphologies differ from undoped material.…”
Section: Diamond Growth and Characterizationmentioning
confidence: 99%
“…This is a source of contamination in the gas phase which leads to boron doping of the diamond films [9]. As shown by Wang et al [10], the addition of boron compounds in a microwaveplasma-assisted CVD system changes the surface morphology and the defect structure of the growing crystallites. Although during the present experiments no clear relation between surface structure and boron content was found, it cannot be excluded that the observed morphologies differ from undoped material.…”
Section: Diamond Growth and Characterizationmentioning
confidence: 99%
“…7 Concerning the doping effects on the growth, it has been reported that the structural perfection of diamond grains is improved for polycrystalline diamond films prepared by chemical vapor deposition (CVD). 8 It was theoretically and experimentally proved that the substitutional incorporation of boron atoms into diamond lattices results in the lattice expansion, because boron having a larger covalent radius (0.88 Å) than that (0.77 Å) of carbon. 9,10 Studies on nanocrystalline diamond (NCD) films have revealed that while the size of diamond grains rarely alters by boron-doping, the doped boron atoms are substitutionally incorporated into the diamond lattices of the grains similarly to the case of polycrystalline diamond films.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate level (1000-5000 ppm B/C) boron addition results in p-type BDD thin films with other characteristics similar to the diamond thin films that will be obtained without boron in the gas phase at the same experimental conditions. High level (>4000 ppm B/C) boron addition results in the loss of crystallinity [31,32]. Still higher level (8000-10000 ppm B/C) disturbs the diamond phase stability.…”
Section: Bdd Thin Films Via In Situ Dopingmentioning
confidence: 99%
“…The conductivity of diamond thin films can be attuned to an application requirement typically by carrying out suitable doping events. Amongst the available conductive (doped, p-and n-type [9][10][11][12][13][14][15][16]) diamond thin films, the p-type semiconducting boron-doped diamond (BDD) thin films [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] are the most popular ones and are being studied extensively. BDD thin films are synthesized by substituting some of the sp 3 hybridized carbon atoms in the diamond lattice with boron atoms.…”
Section: Introductionmentioning
confidence: 99%